Phone-Crossed Lovers: Dehumanizing Technology in Cocteau's and Poulenc's La Voix humaine - Miller Gottlieb, Lynette (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2001)
Forty years after his previous collaboration with his former mentor Jean Cocteau, Francis Poulenc embarked on another joint work with the playwright, the opera La Voix humaine (1958). The sole character is a woman known as Elle, who converses with her former lover on the telephone, a device representative of the negative side of technological progress made during the first few decades of the twentieth century. This study considers the nature of the collaboration between Cocteau and Poulenc, then employs narrative theory to interpret the telephone's power in this drama.